Therapeutic Efficacy of Abdominal Exercise with Bracing in Reducing Diastasis Recti among Postpartum Women: A Literature Review - Raju, Angel; Chauhan, Karishma; Samuel R, Jeffery (INTI International University, 2026)
Diastasis Recti Abdominis (DRA) is a condition commonly found in postpartum women in which the rectus abdominis muscles are separated from each other. As a result of this separation, the abdominal muscles are weakened, and the trunk is rendered unstable. Exercises are the most common treatment for strengthening the abdominal muscles and minimizing the separation between the rectus abdominis muscles. Therefore, the aim of this literature review was to assess the effectiveness of abdominal exercises in combination with bracing in minimizing the separation between the rectus abdominis muscles in postpartum women. Eleven literature articles on the subject matter published between 2014 and 2025 were used in the review. All the articles cited in the literature review showed a significant reduction in the separation between the rectus abdominis muscles in postpartum women who used abdominal exercises in combination with bracing. The findings from the literature review show that abdominal exercises in combination with bracing are an effective treatment for minimizing the separation between the rectus abdominis muscles in postpartum women with DRA. More research is required on the subject matter.